2019
DOI: 10.3168/jds.2018-15063
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal muscle thickness and echogenicity and plasma creatinine concentration as indicators of protein and intramuscular fat mobilization in periparturient dairy cows

Abstract: High-producing dairy cows experience a state of negative energy balance in the periparturient period that is partially addressed by increasing the rate of fat and protein mobilization. Previous studies have focused on the rate of fat mobilization, and consequently the rate of protein mobilization has not been well characterized. The objective of this study was therefore to determine the change in indicators of muscle mass during early lactation using ultrasonographic measurement of muscle thickness and changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 55 publications
7
22
2
7
Order By: Relevance
“…The study reported here was part of a larger study investigating energy and potassium homeostasis in the periparturient period, and the prediction of parturition and dystocia in Holstein–Friesian cattle. These results have been published elsewhere …”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…The study reported here was part of a larger study investigating energy and potassium homeostasis in the periparturient period, and the prediction of parturition and dystocia in Holstein–Friesian cattle. These results have been published elsewhere …”
Section: Methodssupporting
confidence: 55%
“…Cows in the study reported here were in negative energy balance, based on reductions in BFT (46%) and LDT (26%) since parturition . Hypoglycemia (plasma [gluc] < 55 mg/dL) was very common during the study period, being identified in 53% (172/327) of the plasma samples and 79% (81/103) of the cows.…”
Section: Resultsmentioning
confidence: 84%
“…Further investigation into the relationships between muscle mass, serum Creat concentration, serum CK activity, and age appear indicated to identify the preferred analyte to monitor muscle mass in endurance-trained dogs. Ultrasonographic measurement of the cross-sectional area of selected muscles, such as the longissimus dorsi, might be helpful in this matter [46]. Neuter status information would also be beneficial as neuter status affects serum Creat concentration in male and female dogs and serum CK activity in male dogs [11].…”
Section: Plos Onementioning
confidence: 99%
“…The energy status markers (glucose, NEFA, and BHB) showed negative energy balance and lipid mobilization characteristic of transition cows without differences among classes, even though fructosamine, which was previously related to the energy balance markers (Caré et al, 2018), was lower in D animals. After calving, cows with lower D:C also exhibited a more pronounced decrease in plasma creatinine compared with other cows, suggesting a higher muscle mobilization in cows of class D compared with cows of class M and E. Plasma creatinine level in healthy, euhydrated cows is strictly related to muscle mass, and it has been recently suggested as a reliable index to monitor protein mobilization in periparturient cows (Wyss and Kaddurah-Daouk, 2000;Megahed et al, 2019). Therefore, the lower plasma levels of fructosamine and creatinine in D animals suggest a negative relation of D:C with the energy and protein balance of cows during the postpartum period.…”
Section: Discussionmentioning
confidence: 99%